2019
DOI: 10.1101/798769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of protective human antibodies against Plasmodium falciparum circumsporozoite protein repeat motifs

Abstract: Circumsporozoite protein of the human malaria parasite Plasmodium falciparum (PfCSP) is the main target of antibodies that prevent the infection and disease. Protective antibodies recognize the central PfCSP domain, but our understanding of how parasite inhibition is associated with recognition of this domain and with the evolution of potent antibodies remains scattered. Here, we characterized the epitope specificity of 200 human monoclonal PfCSP antibodies. We show that the majority of PfCSP antibodies bind t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 46 publications
(41 reference statements)
5
59
2
Order By: Relevance
“…Our data suggest that somatic mutations of residues that partake in Fab-Fab contacts enhance homotypic interactions and indirectly improve the binding affinity of the mAb to PbCSP. In this aspect, mAb 3D11 binding to PbCSP resembles binding of some neutralizing human mAbs to PfCSP (37, 40, 41). Taken together, these findings indicate that homotypic interactions are a feature by which the mammalian immune system can robustly engage repetitive Plasmodium antigens with high affinity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data suggest that somatic mutations of residues that partake in Fab-Fab contacts enhance homotypic interactions and indirectly improve the binding affinity of the mAb to PbCSP. In this aspect, mAb 3D11 binding to PbCSP resembles binding of some neutralizing human mAbs to PfCSP (37, 40, 41). Taken together, these findings indicate that homotypic interactions are a feature by which the mammalian immune system can robustly engage repetitive Plasmodium antigens with high affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Biophysical studies of the PfCSP central NANP repeat have shown that this region possesses low secondary structure propensities (45, 47–49), and AFM studies on live Pf sporozoites suggest a range of conformations for PfCSP (50, 51). Recent studies have uncovered that some of the most potent antibodies at inhibiting sporozoites are crossreactive with the PfCSP N-junction region that harbors KQPA, NPDP and NVDP motifs interspersed with NANP motifs (39, 40, 43). Our MD simulations of different sub-regions of the PfCSP central repeat including the N-junction provided detailed descriptions of their conformational ensemble and revealed that all sequences possess similar low structural propensity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations